1993
DOI: 10.1177/000456329303000113
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retinol Binding Protein: Stability and Pre-Analytical Handling of Specimens for its Measurement

Abstract: SUMMARY. The stability of retinol binding protein (RBP) in urine has been reassessed and was found to be pH-dependent, diminishing as urinary pH decreased. When urines were incubated at 4°C for 1 week, statistically significant losses of RBP were observed at pH values less than seven, varying in degree in different urines. At 37°C some urine specimens showed minor losses when incubated for periods up to 4 h. This was more marked at pH 5 than pH 7 with maximum losses of 260/0 and 12%, respectively. When adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…We hypothesise that reasons could involve the dissociation of retinol from its binding protein in acidic conditions which increases retinol abundance during extraction. This is supported by the findings of Guy et al [17] who reported that urinary retinol binding protein is pH dependent, and is most unstable at pH 5-7.…”
Section: Effect Of Acid On the Extraction Of Retinol From Dried Plasmsupporting
confidence: 79%
“…We hypothesise that reasons could involve the dissociation of retinol from its binding protein in acidic conditions which increases retinol abundance during extraction. This is supported by the findings of Guy et al [17] who reported that urinary retinol binding protein is pH dependent, and is most unstable at pH 5-7.…”
Section: Effect Of Acid On the Extraction Of Retinol From Dried Plasmsupporting
confidence: 79%
“…To assess the roles of glomerular and tubular function in reduction of urinary protein excretion, we measured the changes of urinary immunoglobulin G (IgG) as a glomerular marker and retinol-binding protein as a tubular marker. Because 24-h urine samples would entail samples remaining at 378C for several hours, which leads to the potential for significant losses of retinolbinding protein in the bladder [22], a random sample during daytime was collected instead. Polyclonal antibodies raised in rabbits against retinol-binding protein were obtained from Assaypro Ulc Company (Winfield, Missouri, USA).…”
Section: Laboratory Testsmentioning
confidence: 99%
“…We are now able to measure specific proteins as markers of glomerular and Correspondence: Mr J M Guy. 668 tubular disease to facilitate the earlier detection of renal disease. For this reason, several workers have advocated the measurement of specific urinary proteins, notably albumin 16 which has been particularly exemplified in the assessment of diabetic nephropathy." 9 The few reports describing the use of specific urine protein measurement in SLE are conflicting.…”
Section: Additional Key Phrases: Glomerular Proteinuria; Tubular Protmentioning
confidence: 99%